2013
DOI: 10.1186/2193-1801-2-684
|View full text |Cite
|
Sign up to set email alerts
|

Parenteral administration of twin-bearing ewes with L-arginine enhances the birth weight and brown fat stores in sheep

Abstract: The objective of this study was to evaluate the effects of parenteral administration of L-arginine (Arg) to well-fed twin-bearing ewes from day (d) 100 of pregnancy to birth on fetal growth, body composition and neonatal behavior. Ewes received an i.v. bolus of either 345 μmol Arg-HCl/kg bodyweight or saline solution (control) 3 times a day. At d 140 of pregnancy, Arg-supplemented and control ewes were euthanized and fetal weight and fetal organ weight recorded, and maternal and fetal plasma concentrations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 46 publications
2
27
2
Order By: Relevance
“…However, in our timecourse trial and previous studies in pregnant ewes, it has been clearly found that Arg concentrations increased during the first 1 to 2 hours after Arg treatment and then declined to baseline levels within more than 4 hours after injection [25,43]. Thus, Arg clearance occurs rapidly in pregnant and nonpregnant sheep.…”
Section: Discussioncontrasting
confidence: 39%
“…However, in our timecourse trial and previous studies in pregnant ewes, it has been clearly found that Arg concentrations increased during the first 1 to 2 hours after Arg treatment and then declined to baseline levels within more than 4 hours after injection [25,43]. Thus, Arg clearance occurs rapidly in pregnant and nonpregnant sheep.…”
Section: Discussioncontrasting
confidence: 39%
“…For example, Chacher et al (2013) suggested that promotion of the synthesis and metabolism of endogenous L-Arginine, through supplementation with feed additives that elevate blood plasma arginine levels, enhanced immunity, reduced SCC, and reduced the incidence of mastitis in sows. McCoard et al (2013) found that administration of L-arginine to Romney ewes improved mammary gland health and decreased SCC in the milk produced. Woloszyn (2007) revealed that the cows with high SCC had a significantly lower concentration of arginine in their blood plasma.…”
Section: Discussionmentioning
confidence: 95%
“…A crucial factor for survival, growth, and development of fetus is a functional placenta for transporting nutrients, respiratory gases, and metabolism products between the maternal and fetal circulations (Wang et al 2012). AR is a nutritionally essential amino acid for the fetus and is a precursor for the synthesis of nitric oxide and polyamines, which are essential for placental growth and function, and growth of new vessels from the existing vasculature and, therefore, for increasing uterine and placental-fetal blood flow (Wu et al, 2004 and2009;Lassala et al, 2010and McCoard et al, 2013. Polyamines play important roles in placental health and development by regulating angiogenesis or new blood vessels formation (Kwon, 2003).…”
Section: Live Body Weight Of Ram Lambsmentioning
confidence: 99%